Terapi Aktivitas Senam Ergonomis terhadap Peningkatan Kemampuan Fungsional Lansia (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to analyze the effect of ergonomic exercise on the Improvement of Functional Ability in the elderly in the Posyandu Elderly Work Area of the Sukamerindu Public Health Center in Bengkulu City, which decreased Functional Ability. The design of this study used a quasi-experimental design with pre-test and post-test without comparison (control) groups. Paired T-test results showed an increase in the value of functional ability with P Value = 0,000